Faire profession de témoignage : les pratiques d’écriture d’Anne-Marguerite Dunoyer (1707-1719) - Marion Brétéché (Etudes Epistémè)
This study of the complete works of Anne Marguerite Dunoyer (1663-1719) deals with the writing practices of a French Protestant exiled in the Dutch Republic. These practices permitted her to live by her pen and to proclaim herself an author. Thanks to her specialization in topical pamphlets and her self-fashioning as a “witness to the politics of her time”, she developed an original point of view. These choices enabled her to take advantage of the specificities of the Dutch book-control system and to become a professional writer.